Pengaruh Karakteristik Pertanian Terhadap Motivasi Masyarakat Menjadi Tenaga Kerja Indonesia di Kecamatan Gondanglegi - Faradiba, Chyntia Dwi; Adrianto, Dimas Wisnu; Subagiyo, Aris (Jurnal Tata Kota dan Daerah, 2013)
Farmland in Gondanglegi District consist of 49% rice field and 21% field and it made Gondanglegi District as one of district that has potential in agriculture. However, there were 2.586 residents in Gondanglegi District which worked as Indonesian Migrant Worker and it made Gondanglegi district as the biggest contributor for Indonesian Migrant Worker in Malang Regency. It means that agriculture development failed to provide decent jobs for the residents which caused livelihood reshuffle in Gondanglegi District. This study aimed to determined primary variables that influenced society motivation to be Indonesian Migrant Worker based on agriculture characteristics (land, human resources, productivity, & income). Descriptive analysis used in this study for exploring agriculture characteristics and multiple linear regression analysis also used for exploring the influence of agriculture characteristic towards society motivation to be Indonesian Migrant Worker. Comparative of the result of multiple linier regression and descriptive analysis of agriculture characteristics are used to verified the influence every variables towards society motivation to be Indonesian Migrant Worker by spatial analysis. The result in this study was primary variable that influenced society motivation for being Indonesian Migrant Worker. Income was the primary variable that influenced society for chosing Indonesian Migrant Worker as livelihood because the more lower income made society motivation as Indonesian workface was bigger. Low income was influenced by marketing management which depend on factory. Besides that, there is no agricultural processing product system made by the society.Keywords: Characteristic of Agriculture, Indonesian Migrant Worker